Financial conservatism and speed of adjustment towards capital structure: Empirical evidence from Pakistan - Ammara Yasmin; Abdul Rashid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This study is the first to empirically examine whether the speed of adjustment (SOA) of capital structure is asymmetric between financially conservative (FC) and non-financially conservative (NFC) firms in Pakistan over the period 1998-2014. Using GMM estimation method for estimating target net debt ratio and OLS for estimating speed of adjustment, we examine when and to what extent these firms adjust their leverage towards the target. The results reveal that the adjustment process is quite asymmetric and the magnitude of the SOA is always greater for NFC than FC firms. We observe that FC firms show higher SOA when they deviate below the target regardless of financial imbalances. In contrast, NFC firms are more responsive to financial deficits irrespective of the deviation from the target. Yet, we show that both FC and NFC firms move with higher SOA towards the target capital structure when they deviate below the target and face financial deficits.
Keywords: 330; financially conservative firms; net debt ratio; net debt target; target capital structure; speed of adjustment